Connectivity and college students' participation in micro-charity: a qualitative study in China. Issue 4 (2nd October 2017) - Lin, Xun; Huang, Hua
Abstract: Traditionally, Chinese people are deeply trapped in an intricate web of guanxi and their charitable commitment is mainly limited within close ties. Recently, the rising social media provides new potential for people's participation in micro-charity online. With connectivity, the socio-technological affordance of social media, people's participation in micro-charity is imbued with distinct meanings from that in traditional charity. This study drew on in-depth interview with eight college students. The results indicate that the participants' engagement and commitment are embedded in their interactive activities and end up having significant consequences both for charity and for themselves. During the process, participants undergo rich subjective experience which is clustered around developing connection, fostering engagement, encouraging collaboration and empowering their selves. This study concludes that people's participation in micro-charity is mixed with connective actions – a hybrid that increasingly applies to life within a space of connectivity in which traditional guanxi is losing its grip on individuals, and blood and clan-ties-based relations are being replaced by large-scale, fluid social networks.